Prevalence of articular cartilage lesions and surgical clinical outcomes in football (soccer) players` knees: A systematic review - Andrade, R.; Vasta, S.; Papalia, R.; Pereira, H.; Oliveira, J. M.; Reis, R. L.; Espregueira-Mendes, J. (Arthroscopy: The Journal of Arthroscopic and Related Surgery, 2016)
Purpose: To systematize the available scientific literature on the prevalence of articular cartilage and/or osteochondral lesions in football (soccer) players' knees, and overview the surgical procedures and functional outcomes and return to sports. Methods: A comprehensive search using Pubmed, Cochrane Library, SPORTDiscus, and CINAHL databases was carried out until September 30, 2015. All English language studies that assessed the outcomes of a surgical technique for the treatment of articular cartilage lesions in football players' knees, with a minimum follow-up of 12 months, were included. The reference list of the most relevant papers was screened. The main outcomes of interest were the clinical, arthroscopy or imaging primary outcomes and the return to sports rate. The methodological and reporting qualities were assessed according to Coleman methodology score. Results: The search provided 485 titles and abstracts. Five studies were eligible for inclusion (mean Coleman score of 37.2 points), comprising a total of 183 football players with a mean age of 25.7 years. A total of 217 articular cartilage and/or osteochondral lesions were reported, where the medial and lateral femoral condyles were the most common sites of lesion. The surgical procedures investigated were mosaicplasty, microfracture, autologous chondrocyte implantation, and chondral debridement. Conclusions:No definitive conclusion could be made in respect to the best current surgical technique for articular cartilage and osteochondral lesions. Microfracture and mosaicplasty can provide a faster return to competition and faster clinical and functional results, whereas autologous chondrocyte implantation and/or matrix-induced autologous chondrocytes implantation procedures can enhance longstanding clinical and functional results.